Exposición Visual al Reforzador Sexual en la Codorniz Japonesa Macho (Coturnix Japonica) (2010)
En este trabajo se presentan dos experimentos con respuesta apetitiva sexual condicionada instrumentalmente, que observaron la discriminación de la magnitud del reforzador sexual en codornices japonesas machos durante varios ensayos. En el primero se comparó la preferencia del macho por exposición visual a ocho hembras contra una hembra, se encontró que los machos prefirieron la mayor magnitud. En el segundo experimento, se midió la preferencia de los machos ante ocho minutos de exposición visual a una hembra contra un minuto a una hembra, los machos prefirieron la magnitud mayor. En los dos experimentos se registró la duración de carrera, no se observó diferencia significativa entre ensayos. Sólo en el experimento uno se hallo diferencia significativa grupal en la duración en la preferencia del volumen menor de hembras. / Abstract: Two experiments were realized to observe reinforcement magnitude effects in male Japanese quail sexual behavior. Both experiments used discrimination conditioning and the males have not sexual contact with any female. In the first experiment 10 male Japanese quails were exposed to 2 reinforcement volume magnitudes: 8 or 1 female Japanese quails during 5 minutes. In the second experiment 10 male Japanese quails were exposed to a female in two temporal conditions: 8 or 1 minute. The preference frequency and duration of running were measure. In the first experiment the preference frequency measure showed a statistically significant difference in the choice, the subjects prefer 8 females; however duration of running measure showed lower durations for 1 female than for 8 females, and this preference was statistically significant different. In second experiment the preference frequency measure showed a statistically significant difference a in the choice, the subjects prefer 8 minutes.